Transcriptional differences between two distinct manganese-containing superoxide dismutase genes in Bacillus cereus - LIU Juan; WANG Song; ZHANG Li-qin; WANG Yong-jun; WANG Qi (浙江大学学报. 农业与生命科学版, 2012)
The promoter activity differences of two manganese-containing superoxide dismutase (MnSOD) genes sodA1 and sodA2 in Bacillus cereus 905 were assayed in vivo by use of lacZ reporter. The results showed that sodA1 and sodA2 were transcripted constitutively during the bacterial growth. The promoter activity of sodA1 were 3-4 times higher than that of sodA2. Compared with wild type, both sodA1 and sodA2 were induced in a MnSOD-deficient strain KOS, which suggested some unknown regularity for sodA1 and sodA2 transcriptions in response to oxidative stress. Additionally, bacterial blue colonies caused by the high β-galactosidase activity under the sodA1-lacZ reporter indicated that sodA1-lacZ reporter was feasible to label B. cereus.